Up-Regulation of Interleukins (ILS) and their Potential Role in the Pathogenesis of Radicular Cyst - Anoosh Qayyum, Amina Shahid, Khalida Anwar, Nusrat Tariq, Sultan Ahmad, Naveed Shuja, Sara Zahid, Sulayman Waquar, Arif Malik (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Study the upregulation of Interleukin levels and their potential role in the pathogenesis of radicular cysts Study Design: Cross-sectional study Place and Duration: Institute of Molecular Biology and Biotechnology (IMBB), The University of Lahore, (9-10 Months) Martials and Methods: Hundred samples were extracted from both diseased and healthy individuals and tissue homogenates were prepared. MDA and LPS were estimated with the help of spectrophotometric method. IL1, IL-6, TNF-α and MMP-9 were determined by their commercial ELISA kits. Results: Malondialdehyde (MDA) was significantly (p=0.033) higher (3.99±0.99 Vs .95±0.011) in diseased group as compared to control. Higher levels of IL-1 (pg/ml) (6.59±1.56 Vs 4.56±1.23), IL-6 (pg/ml) (7.65±1.41 Vs 5.99±0.219) and TNF-α (pg/ml) (31.55±4.55 Vs 20.55±3.28) were recorded in the diseased group. In the group of patients, MMP-9 remained significantly increased when compared with the healthy controls in the case of subjects it remained (93.25±6.48 ng/ml) while in controls they were (47.22±5.29 ng/ml). Likewise in the case of LPS it was significantly increased in the group of radicular cyst (17.25±4.26 pg/ml) as compared to healthy controls (125.25±9.28 pg/ml). Conclusion: Present study indicates the significant correlation of LPS with the pathogenesis of radicular cyst. Moreover, it indicates that as the oxidative stress is increased, it increases the expression of several ILs and MMP-9 that contribute in the pathogenesis of radicular cyst. Further studies may describe the role of lipopolysaccharide and other potential variables to enable better understanding about bone resorption mechanism in periapical cyst development. Keywords: Interleukins, Lipopolysaccharides (LPS), Malondialdehyde (MDA), MMP-9, Radicular Cyst.